Suppression of Brazier Effect in Multilayered Cylinders - Hiroyuki Shima; Motohiro Sato; Sung-Jin Park (Advances in Condensed Matter Physics)
When a straight hollow tube having circular cross-section is bent uniformly into an arc, the cross-section tends to ovalize or flatten due to the in-plane stresses induced by bending; this ovalization phenomenon is called the Brazier effect. The present paper is aimed at theoretical formulation of the Brazier effect observed in multilayered cylinders, in which a set of thin hollow cylinders are stacked concentrically about the common axis. The results indicate that mechanical couplings between stacked cylinders are found to yield pronounced suppression of the cross-sectional ovalization. Numerical computations have been performed to measure the degree of suppression in a quantitative manner and to explore how it is affected by the variations in the bending curvature, the number of stacked cylinders, and the interlayer coupling strength.